URGENSI INTERNALISASI NILAI-NILAI KARAKTER OLEH MASYARAKAT UNTUK MENCEGAH KENAKALAN ANAK - Zaenullah, Zaenullah; Efendiy, Khoirul (FKIP Universitas Wisnuwardhana, 2018)
Character education is very important to prevent child delinquency, especially teenagers. In the era of globalization and gadget addiction, infinite information flow can have a negative influence on children so they do delinquency. Unfortunately, character education in schools is limited to the level of knowing and not at the level of habituation so that character values have not been fully internalized. Society is one of the educational environment, so that people have a moral burden to participate in internalizing character values. Some efforts that can be done by the society to internalize character values in adolescents include optimizing the role of society leaders as motivators and mentors, maximizing the role of youth organizations and functioning mosques not only as places of worship but also as centers for character education with various activities to be carried out. Thus, internalization of character values will occur continuously between the school, family and society environment. Hopefully, delinquency in children can be prevented.Keywords: society’s role, character education, values internalization